Sialolithiasis and its management in two horses - Sagliyan, Aydin; Han, Mehmet Cengiz; Gunay, Cihan (My University, 2009)
Sialoliths were successfully removed surgically in two English horses under xylazine sedation and chloral hydrate anesthesia. No complications were recorded in the post-operative period and the animals recovered uneventfully.
Keywords: Animalia; Equidae